Investigating the Global and Local in Wangchuck Centennial National Park: A Case for the Bhutanese Conservation Actors In-Between - Steele, Anna Lee (Consilience, 2018)
Bhutan is world famous for its approach to both environmental conservation and development, despite being classified as “least developed” by the World Bank as recently as 2016. As Bhutan continues to develop, it has increasingly encountered the colloquially known, but statistically unproven phenomena: that development standards and conservation goals are often in conflict with the needs of rural communities. In the case of such ideological, cultural and economic clashes, this article argues for the necessity of “middle-actors” such as native Bhutanese civil servants, as they are able to navigate the cultural and economic zone “in-between” the international and the local in ways that others cannot.